Educational Impact of Using the VISSIT to Determine Service Delivery Time of Itinerant Teachers of Students With Visual Impairments. (May 2022) - Cihan, Mehmet Akif; Pogrund, Rona L.
High-quality education for students with visual impairments starts with service intensity determination based on the needs of students by teachers of students with visual impairments (Lewis & Allman, 2017; Spungin et al., 2016). Even though the Individuals with Disabilities Education Improvement Act (IDEA) emphasizes addressing students' needs for service delivery (United States Department of Education, 2004), some teachers of students with visual impairments continue taking other factors such as caseload size into account for service intensity determination (Pogrund et al., 2019). Similarly, The Michigan Vision Services Severity Rating Scale (Michigan Department of Education, 2017) does not focus on the individual needs of the students to recommend service time. For example, it considers teachers' availability such as travel time while determining service intensity. It also uses students' visual condition as a criterion, which may not always accurately reflect the needs of the students for service delivery time.